Studies on Growing Stock Estimation of Bambusa bambos in the Forests of Kerala - Krishnankutty, C. N.; Chundamannil, Mammen (Indian Forester, 2011)
Commercially important bamboo, Bambusa bambos (L.) Voss is the abundantly occurring in the forests of Kerala State in India. The average growing stock of B. bambos per ha in different stand density classes in the forests of Kerala was estimated through a statistically designed field survey in natural forests. The average number of culms per hectare ranges from 2741 in pure bamboo patches to 742 in poorly stocked bamboo areas. The estimated average green weight per ha is 147.8 metric tonnes in pure bamboo patches, 83.8 metric tonnes in medium density bamboo stands and 29.4 metric tonnes in areas with poor stocking. In terms of moisture free dry-matter content, the average oven-dry weight per hectare is 80.9 metric tonnes in pure bamboo patches, 45.9 metric tonnes in medium density bamboo stands and 16.1 metric tonnes in areas with poor stocking. The above estimates are useful for assessing the growing stock of bamboo in terms of either green weight or dry weight, when the area under bamboo in the forests in a region is known from field or aerial surveys.